Placental morphological features of small for gestational age preterm neonates born to mothers with pregnancy-induced hypertension - Zhang, Yu; Zeng, Hui-Hui (Frontiers in Pediatrics, 2023)
Small for gestational age (SGA) neonates are often born to mothers with pregnancy-induced hypertension (PIH). Here, we aimed to explore the morphometric characteristics of the placenta during the perinatal period associated with SGA risk in mothers with PIH and identify the risk factors related to SGA. The medical records of 134 neonates born between 28- and 32-weeks’ gestation to PIH mothers were retrospectively analyzed. Placental morphology and umbilical cord (UC) length were compared between the SGA and appropriate for gestational age (AGA) groups. The placenta of the SGA group had a shorter major (15.00 vs. 18.00 cm; z = -6.04, p< 0.01) and minor placenta axes (13.00 vs. 15.00 cm; z = -4.59, p< 0.01), lower weight (300.00 vs. 420.00 g; z = -7.21, p< 0.01), smaller volume (282.00 vs. 396.00 cm3; z = -5.00, p< 0.01), and smaller area (141.00 vs. 212.00 cm2; z = -5.96, p< 0.01) than the AGA group. The UC was significantly shorter (39.00 vs. 44.00 cm; z = -3.68, p < 0.01). Short placental major axis (p= 0.03; odds ratio [OR]: 2.16; 95% confidence interval [CI]: 1.842.63) and low placental weight (p< 0.01; OR: 2.68; 95% CI: 2.662.70) were independent risk factors for SGA in premature newborns of PIH mothers. A major axis shorter than 15.5 cm or placental weight lower than 347.50 g at birth was related to a greater risk of SGA infants born to PIH mothers. As a predictor in prenatal ultrasound, the major axis is more helpful for precise prenatal pre-evaluation of vulnerable SGA preterm neonates with PIH mothers.